2009
DOI: 10.1371/journal.pcbi.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Variability and Effort as Determinants of Coordination

Abstract: When coordinating movements, the nervous system often has to decide how to distribute work across a number of redundant effectors. Here, we show that humans solve this problem by trying to minimize both the variability of motor output and the effort involved. In previous studies that investigated the temporal shape of movements, these two selective pressures, despite having very different theoretical implications, could not be distinguished; because noise in the motor system increases with the motor commands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 21 publications
12
101
3
Order By: Relevance
“…For the task constraints, the results revealed that the system adopted the task efficiency strategy (minimum muscle force output) rather than the strategy of minimizing task variance. The results are consistent with previous findings showing preference on task efficiency over other minimization criteria, such as movement time (Lee et al 2007;Nelson 1983) and task variability (O'Sullivan et al 2009). On the task efficiency constraint, the results revealed that coefficient-dependent model was the best fitted model in that the optimal force sharing pattern predicted by the task constraint scales with the coefficient ratios imposed on the finger forces.…”
Section: Experimental Results and Model Predictionssupporting
confidence: 92%
“…For the task constraints, the results revealed that the system adopted the task efficiency strategy (minimum muscle force output) rather than the strategy of minimizing task variance. The results are consistent with previous findings showing preference on task efficiency over other minimization criteria, such as movement time (Lee et al 2007;Nelson 1983) and task variability (O'Sullivan et al 2009). On the task efficiency constraint, the results revealed that coefficient-dependent model was the best fitted model in that the optimal force sharing pattern predicted by the task constraint scales with the coefficient ratios imposed on the finger forces.…”
Section: Experimental Results and Model Predictionssupporting
confidence: 92%
“…Variability in force production ("motor noise") has also been hypothesized as a cost to optimize (Harris and Wolpert, 1998;Haruno and Wolpert, 2005;O'Sullivan et al, 2009;Diedrichsen et al, 2010) but it covaries with muscle activity under natural conditions (Jones et al, 2002). To dissociate these factors, we manipulated the virtual biomechanics to increase the signaldependent noise associated with muscle activation in one of the five muscles (i.e., an extensor muscle, n ϭ 3; or a flexor muscle, n ϭ 3).…”
Section: Adaptation To Novel Virtual Biomechanics With Motor Noise-exmentioning
confidence: 99%
“…Resolution of this redundancy is a fundamental problem of biological motor control (Bernstein, 1967) that must also be addressed for the design of robotic and prosthetic systems that mimic or restore human movement (Loeb and Davoodi, 2005). The computational framework of optimal control theory has gained influence as a general theory of motor coordination because it can specify uniquely how behavioral goals should be achieved by minimizing costs such as the effort or variability of movement (Pedotti et al, 1978;Crowninshield and Brand, 1981;Davy and Audu, 1987;Loeb et al, 1990;Harris and Wolpert, 1998;Todorov and Jordan, 2002;Scott, 2004;Todorov, 2004;O'Sullivan et al, 2009;Diedrichsen et al, 2010). Although some aspects of natural motor behavior, such as typical patterns of muscle activity, are consistent with the output of optimal control models (Fagg et al, 2002;Haruno and Wolpert, 2005;Diedrichsen et al, 2010), how the nervous system generates this behavior is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This also contributes to movement variability. Most optimization approaches predict average behavior (Collins 1995;Engelbrecht 2001;Harris and Wolpert 1998;Scott 2004) assuming that the nervous system minimizes variability as a limiting constraint (Harris and Wolpert 1998;Körding and Wolpert 2004;O'Sullivan et al 2009). However, recent work demonstrates that humans instead often exploit redundancy to regulate variability in ways that help maximize task performance (Cusumano and Cesari 2006;Latash et al 2002;Todorov and Jordan 2002) while minimizing control effort.…”
mentioning
confidence: 99%